Vitrification of Excised Embryos of Jackfruit (Artocarpus Heterophyllus Lamk) - Wong, Lay Yieng (2000)
This study was carried out to evaluate the potential of vitrification technique for germplasm conservation of jackfruit. The effects of loading solutions and vitrification solutions on survival of jackfruit embryos were evaluated. The first experiment was to study the effects of different loading solutions during vitrification. The embryos were treated with six different loading solutions, followed by exposure to Plant Vitrification Solution 2 (PVS2) before plunging into liquid nitrogen. Results show that without freezing, all the loading solutions did not show deleterious effect on jackfruit embryos as high survival ranging from 81-96% was obtained. On freezing, embryos loaded with 25% PVS2 gave the highest viability (43.3%) and thus selected as the best loading solution for jackfruit embryos for the ensuing experiments. In the second experiment, the embryos were loaded with 25% PVS2 for 0, 8, 12, 14, 16, 18 and 20 hours to determine the optimum time of loading. On vitrification, 12, 14 and 16 hours of loading were equally advantageous, but "14 hours showed the highest with 18.3% viability and 13.3% survival This was then chosen as the optimum time of exposure for the following experiments. The third experiment was to evaluate the effects of different vitrification solutions on survival of jackfruit embryos. On freezing, embryos treated with L Solution gave the highest viability (30%) and survival (24%), which were significantly better than PVS2 and Watanabe Solution. This was thus selected as the most effective vitrification solution for jackfruit embryos. Having determined the best vitrification solution, the fourth experiment assessed the different time of exposure to L Solution, whereby, the embryos were treated for 0, 15, 30, 45, 60, 75, 90, J05 and 120 minutes before freezing. Without freezing, high viability (94.6-100%) was obtained up to 120 minutes exposure. Following freezing, percentage viability increased with increasing time and reached an optimum of 47.4% after 75 minutes before decreasing to only 6.8% viability after 120 minutes exposure. It was concluded that loading with 25% PVS2 for 14 hours, followed by exposure to L Solution for 75 minutes was optimum for vitrification of jackfruit embryos. Viability and survival 47.4% and 35.4% respectively can be obtained.